(3eSGaI BefIs (3EOdjdc MJi jSJeQ GdMH Edi GdCHOs - (3SdWGf, YRIs; (3EHQGgje, RjGOs ((3GdLjRI, eUQs (3HjJ GdjGSejf ddfTQ hGdJhRjYs, 2025)
(3gd jecf ddMH Cf jchf CcKQ ef eLQO TYhQ YGHQ? gd jecf Cf jJMhd Edi af eJbf jKQj GdMjGI hjLYdgG CcKQ YekbG hLeGdG? aj (B"(3eSGaI BefI(B: (3Odjdc MJi jSJeQ GdMH Edi GdCHO(B"(3, JCNPfG GdcGJHI YRI SdWGf aj QMdI BSQI OGNd OgGdjR GdYdGbGJ GdYGWajI, eSJYQVkI JaGUjd GdMH GdCcKQ NaGA hJYbjOG(B. (3HCSdhHgG GdYPH hGdadSaj, JbOe QDjI LOjOI dage GdMH cbhI eJLOOI JJWdH GdMceI hGdhYj dJROgQ , SJLO Hjf WjGJ gPG GdcJGH ELGHGJ Ydi CSFdJc GdYGWajI GdCcKQ MjQI, hSJJYde cjajI GdJaQjb Hjf GdMH hGdGMJjGL, hcjajI HfGA LShQ GdJaGge Hjfc hHjf TQjcc, eY GdMaGX Ydi TZa OGFe hSW OhGeGJ GdMjGI(B. (3gPG GdcJGH djS eLQO Odjd, Hd gh MhGQ eeJY Hjfc hHjf CYXe eTGYQ GdEfSGfjI, edjA HGbJHGSGJ COHjI hCacGQ adSajI edgeI(B... (3EPG cfJ JHMK Yf eaJGM ddMaGX Ydi GdMH cWGbI eJhgLI heUOQ OGFe ddEdgGe, aEf gPG GdcJGH SjefMc GdCOhGJ GdJj JMJGLgG dJYjT JLQHI MH MbjbjI heJhGRfIs
Keywords: (3GdMHs; (3GdSYGOIs; (3GdYdGbGJ GdEfSGfjIs; (3GdYhGWas